2 Incidental coronary artery calcification detection on non-cardiac CT. (7th October 2015) - Giblin, G; Sharma, N; McClelland, S; Hennessy, B; Collison, D; Fitzpatrick, N; Salim, T; Hussein, H; McAdam, BF
Abstract : Aims: The aim of this three month retrospective study was to evaluate the incidental prevalence and burden of coronary artery calcification on CT Pulmonary Angiography (CTPAs) used for the assessment of patients presenting with chest pain suspicious for PE and whether this finding was reported upon by Radiologists. Methods: The National Integrated Medical Imaging System (NIMIS) was manually searched to ascertain all CTPA examinations performed in our institution from 01/07/2014 to 30/09/2014. The Radiologist issued reports were analysed and the images of selected studies were reviewed as described below. Results: 261 CTPAs were performed over this three month period on 257 patients and 104 of these scans were performed on patients between the ages of 40 and 70 which were selected for this review. Of these, 53 were male and 51 were female with a mean age of 57.09 years. Only 25/104 (24%) of these scans commented on the presence of coronary artery calcification and none commented on the absence of calcification. Of the 25 (24%) positive reports, 10 (40%) commented on presence only without localising it or grading its severity, while 10 (40%) reported LAD disease and only 4 (16%) reported three vessel calcification. A total of 7 (28%) reports graded the calcification as severe. The images of the 79/104 (76%) remaining CTPAs whose reports did not comment on coronary calcification were reviewed. 8 (10.1%) were uninterpretable due to either artefact from motion/pacing leads or due to the presence of contrast in the coronary system and these were excluded from the analysis. 25/79 (31.6%) of these CTPAs had calcification of varying degrees present. 5 (20%) had left main deposits while 9 (36%) had three vessel calcification (LAD, LCx and RCA). The LAD was the most commonly involved vessel, with lesions detected in 20/25 scans. 2 patients had evidence of previous stent placement in the LAD. Calcification in the RCA was difficult to visualise well in most cases due to close proximity to contrast filling both the right atrium and ventricle. In summary only 24% of Radiologist reported CTPAs commented upon the presence of coronary artery calcification, while a further 24% of CTPAs were found to have significant calcific coronary disease with 20% of these having left main disease and 36% having three vessel disease. Conclusions: This initial study demonstrates significant variance in reporting of incidental coronary artery calcification in non-cardiac CT in patients between 40–70 years being assessed for chest pain for suspected PE. A longer prospective study is planned to evaluate if such findings have incremental clinical benefit in identifying a cardiac aetiology for chest pain syndromes in these patients and to correlate such findings with clinical outcomes.